2011
DOI: 10.1186/2045-8118-8-8
|View full text |Cite
|
Sign up to set email alerts
|

The CNS microvascular pericyte: pericyte-astrocyte crosstalk in the regulation of tissue survival

Abstract: The French scientist Charles Benjamin Rouget identified the pericyte nearly 140 years ago. Since that time the role of the pericyte in vascular function has been difficult to elucidate. It was not until the development of techniques to isolate and culture pericytes that scientists have begun to understand the true impact of this unique cell in the maintenance of tissue homeostasis. In the brain the pericyte is an integral cellular component of the blood-brain barrier and, together with other cells of the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 156 publications
5
133
1
1
Order By: Relevance
“…Loss of PCs results in a focal increase in BBB permeability (Bonkowski et al, 2011). A close correlation between PC density and BBB permeability has been reported in PC-deficient adult mice (Armulik et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of PCs results in a focal increase in BBB permeability (Bonkowski et al, 2011). A close correlation between PC density and BBB permeability has been reported in PC-deficient adult mice (Armulik et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Последние данные свидетельствуют о том, что нейротрофический фактор головного мозга, секретируемый астроцитами, способствует созреванию клеток-предшественников олигодендроцитов в период восстановления при ише-мическом повреждении БВГМ [90]. В предыдущих рабо-тах также показали, что взаимодействие между астро-цитами и перицитами регулирует выживаемость ткани в центральной нервной системе [91], и что взаимо -действие между астроцитами и эндотелием оказыва-ет влияние на ГЭБ при физиологических и патологи-ческих состояниях [92]. Модели с участием КСГПИ также свидетельствуют об изменении взаимодейст-вия между глией и эндотелием и повышении прони-цаемости ГЭБ.…”
Section: важная роль клеточных компонентов гэб при бмцсunclassified
“…Recent evidence suggests that brain-derived neurotrophic factor secreted by astrocytes promotes oligodendrocyte precursor cell maturation during the recovery from WM ischemic injury. 90 Previous reports have also demonstrated that astrocyte-pericyte cross talk regulates tissue survival in central nervous system, 91 and that astrocyte-endothelial interactions influence the BBB under both physiological and pathological conditions. 92 SHR-SPs also provide evidence of altered glial-endothelial interactions and BBB leak.…”
Section: Important Roles Of Cell Components Of Bbb In Svdmentioning
confidence: 99%
“…Pericytes are considered relatively undifferentiated connective tissue cells associated with the walls of small blood vessels and supporting other cells [65]. Mesenchymal stem cells (MSCs) with similar characteristics and developmental potentials have been obtained from several organs [66].…”
Section: Pericytes Are Stem Cellsmentioning
confidence: 99%